2009
DOI: 10.1080/09540120902803216
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Malay version of WHOQOL-HIV BREF in patients with HIV infection

Abstract: This study determines the validity and reliability of the Malay version of the World Health Organization Quality of Life (WHOQOL) assessment instrument in patients with human immunodeficiency virus (HIV) infection. A cross-sectional study on 157 patients with HIV seen at the Infectious Disease Unit, Hospital Raja Perempuan Zainab II, Kota Bharu, Kelantan was conducted. Factor analysis identified five major domains: physical needs, spirituality, social relationship, psychological, and environment. Significant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
43
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 22 publications
16
43
0
7
Order By: Relevance
“…Similar to the results reported in Portugal, Taiwan and Malaysia, our study shows that the WHOQOL-HIV BREF has good psychometric properties (18)(19)(20). The CVRs for individual items of WHOQOL-HIV BREF were in the acceptable range, which indicates that each item measures the QOL in HIV/ AIDS patients as intended.…”
Section: Discussionsupporting
confidence: 73%
“…Similar to the results reported in Portugal, Taiwan and Malaysia, our study shows that the WHOQOL-HIV BREF has good psychometric properties (18)(19)(20). The CVRs for individual items of WHOQOL-HIV BREF were in the acceptable range, which indicates that each item measures the QOL in HIV/ AIDS patients as intended.…”
Section: Discussionsupporting
confidence: 73%
“…Similar effects in these items have been previously reported [13]. In line with prior validation studies [14,15], no floor and ceiling effects were observed on QoL domains. As ceiling effects are population dependent [22], the observed effects in individual items may be related to the fact that our sample comprised a relatively larger number of middle-aged participants rather than the elderly.…”
Section: ) All Whoqol-hiv-bref Domains and Overallsupporting
confidence: 78%
“…Evidence for convergent validity is supported by significant correlations with the general facet of QoL and the self-reported perception of general health. This pattern of associations was also demonstrated in other validation studies [13,15], and the strength of the associations was comparable to the reported in those studies. Potential limitations imposed by the sample, the sampling strategy and the study design should be acknowledged.…”
Section: ) All Whoqol-hiv-bref Domains and Overallsupporting
confidence: 75%
See 1 more Smart Citation
“…There are 31 items with a five (5) point Likert scale (one to five) validated in English and Bahasa Malaysia (WHO 2002;Saddki et al 2009 (Saddki et al 2009). In addition to the five domains, it also has two (2) items, which assesses general QOL and health perception (items 1 and 2).…”
Section: Methodsmentioning
confidence: 99%